IMPACT OF SINGLE BULB GARLIC (ALLIUM SATIVUM VAR. SOLO) ON THE NUMBER OF LEYDIG AND SERTOLI CELLS IN RATS - Ika Buana Januarti; Fadzil Latifah; Nur Fidia Fatmawati (Jurnal Farmasi Sains dan Praktis, 2021)
Single garlic bulb has been studied as aphrodisiac, this is related to the presence of secondary metabolites flavonoids, alkaloids, and saponins. The metabolite content of single garlic tuber ethanolic extract (EEUBPT) will be investigated for its effect on the histopathological picture and the number of Leydig cells and testicular Sertoli cells in rats. Sample research consist of 25 Wistar rats aged 3-4 months divided into 5 groups. Group I was negative control given 0.5% Na-CMC; group II (positive control) was given Jamu Pasak bumi. Groups III, IV, and V were each given EEUBPT at doses of 450 mg/kgBB, 900 mg/kgBB, dan 1350 mg/kgBB of body weight. Each group was given treatment for 14 days, then the testes were taken on the 14th day. The results were analyzed using the One Way Anova parametric test (p <0.05) and post hoc. The ethanolic extract of a single garlic bulb affected the number of Leydig cells at a dose of 1350 mg of body weight but did not significantly influence the number of Sertoli cells.